Expanding Balance Scorecard to Islamic Business Performance Model on Indonesian Muslim Entrepreneurs: Evidence in Southeast Sulawesi - Sitti Zakiah Ma'mun; Abdul Rahman; Ahmad Muhlis Nuryadi; La Ode Alimusa Musa (Agregat: Jurnal Ekonomi dan Bisnis, 2021)
The purpose of this study is to determine the dimensions of the business performance of Muslim entrepreneurs in Southeast Sulawesi to running a sustainable and competitive advantage. The specific objective is to find a model of alternative business performance measurement of Muslim entrepreneurs which is the development model of Balanced Scorecard by incorporating the factors of shariah such as worship and lawful approach. The method used in this research is Exploratory Factor analysis. The sampling method is non-probability sampling with 120 samples collected through survey questionnaires. Based on the results of the discussion, it can be concluded that three main factors determine business performance; integrated business strategy factors, internal business targets& encouragement, and Islamic business practice. Thus the integration of the business orientation with the material approach to business practices based on Islamic business principles such as halal product orientation and worship motivation can improve the performance of competitive and sustainable SMEs. Keywords: Balanced Scorecard; Islamic business performance; Muslim entrepreneurs